Аналіз ефективності використання аутсорсингу у господарській діяльності підприємств - Дідух, О. В. (Видавництво Львівської політехніки, 2012)
Проаналізовано основні підходи до оцінювання ефективності використання аутсорсингу у господарській діяльності підприємств, виявлено їх недоліки, а також визначено систему показників оцінки результативності аутсорсингу залежно від видів і етапів його впровадження. The article examines and analyses the basic approaches to defining the effectiveness of outsourcing in economic activity of enterprises, the major drawbacks are found. Also the system of indexes of assessing the effectiveness of outsourcing, depending on the kinds and stages of its implementation, are defined.
Analysis of efficiency of the use of autsorsing іn economic activity of enterprises
Keywords: аутсорсинг; ефективність; види аутсорсингу; аутстафінг; виробничий аутсорсинг; аутсорсинг бізнес-процесів; ІТ-аутсорсинг; outsourcing; efficiency; types of outsourcing; outstaffing; manufacturing outsourcing; outsourcing business process; IT outsourcing